MENUMBUHKAN CIVIC VALUES DIKALANGAN MAHASISWA: IKHTIAR MENANGKAL RADIKALISME - Biyanto, Biyanto (Indonesia Defense University, 2013)
This research discusses efforts to develop civic values spirit for college students. This is important to deter radicalist thought and act in education sphere, such as gangs fight, demonstration, anarchist action, and also the involvement of students in radical Islamic movement, like â€œIslamic Indonesian Stateâ€. As religion based on radical phenomenon occurs within society, it is important to agree upon diversity. Therefore, the civic culture should be strengthened, such as values of democracy, pluralism and multiculturalism, involving mass media, mass organization, and education institutions. Students are the most important element to be involved in developing civic culture movement. In high level education, college students could be a civic education agent to minimize potential radicalism by giving them comprehensive civic knowledge. Furthermore, the values are actuated into civic disposition action and mindset, as well as daily actuation of civic skills. The college studentsâ€™ role is significantly important by referring to its historical facts, academic culture and an ability to build network. Unfortunately, nowadays, many students are trapped into practical politics and culturally trapped. While actually the cultural role of students can be effectively deter radicalism potential. The role of students is mediator of cross cultural and religion dialogue, formally and informally.Â Keywords: civic values, students, terrorism, deradicalisation